Peningkatan Pengetahuan mengenai Bahaya dan Risiko Gangguan Pernapasan pada Pengemudi Ojek Online - Arleen Devita; Yuliana; Ida Effendi; Hans Utama Sutanto; Meiyanti (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
Jakarta is listed as one of the cities in the world with the most polluted air quality, with an annual average PM 2.5 of 49.4 g/mÂ³ in 2019. The sources of air pollution in Jakarta among others are the large number of motor vehicles that are not in accordance with the guidelines of safe vehicles for the environment. Not to mention air pollution from industries and factories fueled by coal or other fossils. Online motorcycle taxi drivers are a profession that is at risk of experiencing the effects of this air pollution. Respiratory disorders that can occur such as acute respiratory infections, chronic obstructive pulmonary disease (COPD), decreased lung function and lung malignancy. To reduce the risk of respiratory problems that can arise in online motorcycle taxi drivers, efforts are being made to prevent and stop exposure to air pollutants through counseling activities which carried out on November 12, 2023. This activity was attended by 42 online motorcycle taxi drivers. Participants' knowledge was assessed by pre-test and post-test using the Google form to assess participants' cognitive changes. From the results of the pre-test and post-test evaluation, it was found that there was an increase in knowledge about the risks and respiratory tract disorders that could arise, namely 25.5%, with an increasing percentage of correct answers of pre-test and post-test ranging from 4.8 % - 40.5%. It is hoped that this increased knowledge will change the behavior of online motorcycle taxi drivers to always pay attention of prevention and stop exposure to air pollutants.